Understanding mental health challenges and associated risk factors of post-natural disasters in Bangladesh: a systematic review - Karim, Md. Zawadul; Al-Mamun, Md.; Eva, Maliha Azad; Ali, Md. Hazrat; Kalam, Abul; Uzzal, Nurul Islam; Das, Pranto Kumer (Frontiers in Psychology, 2024)
Background and Objectives: Natural disasters are harmful occurrences caused by the Earth's geological and meteorological processes. Bangladesh is recognized as one of the country's most vulnerable to natural disasters. Therefore, the people of Bangladesh remain at high risk of natural disasters. However, no study has been conducted in Bangladesh to provide an overall perspective on mental health issues that arise after natural disasters. Thus, this systematic review aims to identify all mental health issues and related risk factors brought on by natural disasters in Bangladesh.Methods: Between April to May 2024, a systematic search was conducted across many databases, including PubMed, following the PRISMA guideline. Ultimately, 17 publications were included in this study.The findings reveal that depression, anxiety, stress, suicidal ideation, post-traumatic stress disorder, major depressive disorder, generalized anxiety disorder and sleep disturbances are found as major risk factors for natural disasters. Prevalence of depression, anxiety and, stress, suicidal ideation ranges from 16.3% to 92.71%, 6% to 92.19%, 32.41% to 58%, 10.9% to 57.5% among people as consequences of natural disasters like heatwaves, cyclones, flood, river bank erosion etc.There are some associated risk factors which provoke prominent mental health problems, including (i) Demographic factors (age, gender, marital status, number of children, lower education, living location, living infrastructure, family conflicts, family member death, land for cultivation, loss of domestic animals), (ii) socio-economic factors (environmental settings, social support, disaster warning system, displacement, food crisis, financial support, income loss, vulnerable livelihoods) (iii) behaviour and health-related factors (behaviour pattern, physical injury during natural disaster, physical disability), (iv) other factors (increased temperature, living together, lower social class).People affected by natural disasters are often viewed in terms of their physical damage, while their mental health is always ignored.Calculative measures are needed to create an overall picture of the effect of natural disasters on people's mental health in Bangladesh. Therefore, the government needs to consider establishing potential measures to lessen the impact of natural disasters on people's mental health.